Peran Musyrif Dalam Meningkatkan Disiplin Ibadah Santri Di Pondok Pesantren Muhammadiyah Darul Arqom Al Hijrah Lil 'Ulumil Islamiyah Putra Karanganyar Tahun 2017 - Ridho, Muhammad Rasyid; , Dr. Ari Anshori, M.Ag (2017)
Musyrif is a close person in Muslim boarding school whose role is very important to close and control every parts of everyday activities. Musyrif is selected by the chief of Muslim boarding school/ kiai who gives mandate and wrapped around and also believed to observe and control student's activities. One of the character of musyrif is to control and develop of student in discipline in religious service. Development of discipline in religious service is an effort to implant the loyality for certain Islamic Law of Allah Swt until being receptable and becaming a behavior value and became habitual in daily activities. In this research, musyrif of Darul Arqom Muhammadiyah Boarding School al-Hijrah lil 'Ulumil Islamiyah Putra Karanganyar has character that is very important in develop of discipline in religious service of student, and in that implementation there are some problems which faced by the musyrif so the research question which study is about: How to develop function of musyrif in discipline of religious service and what the problems which faced by the musyrif to develop discipline of religious service of students in Darul Arqom Muhammadiyah Boarding School al-Hijrah lil 'Ulumil Islamiyah Putra Karanganyar. The purpose of this research is to know and describe the character and function of musyrif and the problems which are faced in developing discipline of religious service of students in Darul Arqom Muhammadiyah Boarding School al-Hijrah lil 'Ulumil Islamiyah Putra Karanganyar. There are some benefit of this research, they are: (1) Theoritically, to increase treasure of knowledge especially on function of musyrif in developing discipline of religious service of students; (2) Practically, could give benefit, contribution of idea, and as material review for boarding school especially on musyrif to develop discipline of religious service of students. This research is a field one which use descriptive qualitative method. Then method of collecting data used are, observation, interview dan documentation and the analysis of data used is inductive method. Based on the result of the research of data analysis, it can be concluded that the musyrif in development of discipline religious service of students in Darul Arqom Muhammadiyah Boarding School al-Hijrah lil 'Ulumil Islamiyah Putra Karanganyar with apply some elements and forms/ discipline method, they are: making rules, giving punishment and achievement, also motivation, give habitual, became example, and give attention. There are some problems which are faced by musyrif, they are there is no mosque private facility yet, there is enough consciousness from students, and musyrif activities out of boarding school. Keywords: Character of Musyrif, Discipline of Religious Service, Students